Metal-polypyridyl complexes mimicking electronic functions - Kaur, Rajwinder; Singh, Bijai; Singh, Vikram; Zharnikov, Michael; Chandra Mondal, Prakash (Coordination chemistry reviews, 2024)
The assembly of functional molecules on conductive or dielectric substrates represents a promising avenue for employing molecule-centric technologies, encompassing sensor development, electrochromism, memory, and the facilitation of charge and spin transport at the nanoscale. The respective assemblies exhibit robust physical and chemical properties, intrinsic to the nature of the molecules involved in the functionalization of the substrate. Within the spectrum of available molecules, metal-polypyridyl complexes have emerged as one of the most promising systems for generating functional, surface-bound assemblies, encircling monolayers to oligomer films prepared through pre-functionalization methodologies. The advantages of these complexes include their inherent versatility stemming from facile synthesis, appreciable stability, and tuneable optoelectronic properties encompassing rich redox chemistry, luminescent emissions, excited state longevity as well as the possibility to realize stimuli-controlled electron and energy transfer. The present review aims to delve into the nuanced traits and applications of surface-bound metal-polypyridyl complexes, elucidating their electrical characteristics and practical implementations in devices through pertinent and illustrative examples in the field of molecular electronics.
Gesehen am 08.01.2025